Pengaruh Penggunaan ZPT Organik dengan Metode Sayatan Celah Terhadap Sambung Pucuk Durian (Durio zibethinus Murr.) - Margareta Widiani; Kiki Amelia; Wilna Sari; Santi Diana Putri (JURNAL AGROPLASMA, 2026)
Durian (Durio zibethinus Murr.) is a tropical fruit commodity with high economic value and increasing market demand. However, increasing durian production in Indonesia still faces obstacles, particularly the limited availability of high-quality seedlings. Data from the Sijunjung Regency Central Statistics Agency (2024) shows that durian production fluctuates, namely 31,043 tons in 2022, increasing to 36,107 tons in 2023, then decreasing to 34,177.40 tons in 2024. This condition indicates the need for improvements in cultivation technology, especially in the seedling supply stage. Vegetative propagation through grafting techniques using the cleft grafting method is an effective alternative because it can produce uniform seedlings and accelerate the fruiting period. The success of grafting can be improved through the use of natural organic growth regulators (ZPT), such as coconut water, shallot extract, bean sprout extract, and bamboo shoot extract. This study aims to determine the effect of various types and doses of organic ZPT on the success and growth of durian grafting and to determine the best ZPT. The study used a randomized block design with five treatments and five replicates. The treatments consisted of a control without PGR, 250 ml/plant of red onion extract, 200 ml/plant of bean sprout extract, 250 ml/plant of coconut water, and 250 ml/plant of bamboo shoot extract. The data were analyzed using ANOVA, and if there were significant differences, they were followed up with Duncan's multiple range test at a 5% level. The results showed that all treatments produced a 100% survival rate. Organic PGRs had a significant effect on the number of leaves and upper stem diameter, but no significant effect on the increase in shoot length and lower stem diameter. Bean sprout extract produced the highest number of leaves, while coconut water produced the largest upper stem diameter. Keywords: cuttings, durian, growth regulators, organic plant, seeds, slits